A comparative case study of two models of a clinical informaticist service. Issue 7336 (2nd March 2002) - Greenhalgh, Trisha; Hughes, Jane; Humphrey, Charlotte; Rogers, Stephen; Swinglehurst, Deborah; Martin, Peter
Abstract: Objectives: To describe and evaluate two different models of a clinical informaticist service. Design: A case study approach, using various qualitative methods to illuminate the complexity of the project groups' experiences. Setting: UK primary health care. Interventions: Two informaticist projects to provide evidence based answers to questions arising in clinical practice and thereby support high quality clinical decision making by practitioners. Results: The projects took contrasting and complementary approaches to establishing the service. One was based in an academic department of primary health care. The service was academically highly rigorous, remained true to its original proposal, included a prominent research component, and involved relatively little personal contact with practitioners. This group achieved the aim of providing general information and detailed guidance to others intending to set up a similar service. The other group was based in a service general practice and took a much more pragmatic, flexible, and facilitative approach. They achieved the aim of a credible, acceptable, and sustainable service that engaged local practitioners beyond the innovators and enthusiasts and secured continued funding. Conclusion: An informaticist service should be judged on at least two aspects of quality—an academic dimension (the technical quality of the evidence based answers) and a service dimension (the facilitation of questioning behaviour and implementation). This study suggests that, while the former may be best achieved within an academic environment, the latter requires a developmental approach in which pragmatic service considerations are addressed.